2017
DOI: 10.1111/pcmr.12614
|View full text |Cite
|
Sign up to set email alerts
|

Targeting cholesterol transport in circulating melanoma cells to inhibit metastasis

Abstract: Despite recent breakthroughs in targeted- and immune-based therapies, rapid development of drug resistance remains a hurdle for the long-term treatment of patients with melanoma. Targeting metastatically spreading circulating tumor cells (CTCs) may provide an additional approach to manage melanoma. This study investigates whether targeting cholesterol transport in melanoma CTCs can retard metastasis development. Nanolipolee-007, the liposomal form of leelamine, reduced melanoma metastasis in both a novel in vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…Evidence has emerged to indicate that increased lipids and cholesterol, which are correlated with elevated oncogenic growth signaling, such as PI3K-AKT and MAPK signaling in cancer cells, are now considered a hallmark of cancer aggressiveness [ 14 , 20 ]. Indeed, many reports have shown that cholesterol-lowering drugs, such as atorvastatin, lovastatin, and simvastatin, inhibit cancer cell growth and invasiveness via the suppression of oncogenic signaling in HCC, melanoma, glioma, and ovarian cancer [ 21 , 22 , 23 , 24 ]. On this basis, the inhibitory effect of emodin on oncogenic growth signaling in HCC cells was evaluated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence has emerged to indicate that increased lipids and cholesterol, which are correlated with elevated oncogenic growth signaling, such as PI3K-AKT and MAPK signaling in cancer cells, are now considered a hallmark of cancer aggressiveness [ 14 , 20 ]. Indeed, many reports have shown that cholesterol-lowering drugs, such as atorvastatin, lovastatin, and simvastatin, inhibit cancer cell growth and invasiveness via the suppression of oncogenic signaling in HCC, melanoma, glioma, and ovarian cancer [ 21 , 22 , 23 , 24 ]. On this basis, the inhibitory effect of emodin on oncogenic growth signaling in HCC cells was evaluated.…”
Section: Resultsmentioning
confidence: 99%
“…Experimental or clinical evidence has previously shown that high levels of blood cholesterol accelerate hepatocarcinogenesis and lead to poor clinical outcomes in patients with HCC [ 30 , 31 ]. Indeed, the anti-cancer and anti-metastatic effects of cholesterol-lowering drugs, such as simvastatin, lovastatin, and pitavastatin, which are mediated through suppression of the AKT and STAT3 pathways, have been shown in HCC, renal cancer, malignant melanoma, and ovarian cancer [ 22 , 23 , 24 , 32 , 33 , 34 ]. Our results show that emodin has a cholesterol-lowering effect through the suppression of SREBP-2 transcriptional activity and its cholesterogenic gene expression in HCC cells.…”
Section: Discussionmentioning
confidence: 99%
“…Apolipoprotein B-100 (APOB) is a receptor for cholesterol which has been shown to increase melanogenesis 68 and targeting cholesterol transport in melanoma CTCs was shown to retard metastasis development 69 . This may be in line with current results of increased APOB expression in poor survival.…”
Section: Resultsmentioning
confidence: 99%
“…Among the identified lysosomotropic compounds, leelamine (dehydroabietylamine), a lipophilic diterpene amine phytochemical with a pKa of 9.9, is a natural compound extracted from the bark of pine trees [28,43]. Leelamine (structure shown in Figure 1), which was previously reported as having a weak agonistic effect on cannabinoid receptors and limited inhibitory effects on pyruvate dehydrogenase kinases (PDKs) [28,44], has caught particular attention for its lysosomotropic property and significant inhibitory effects on proliferation and tumorigenesis [43,45,46] in human breast cancer cells [47], melanoma cell lines [28,43,48,49], and prostate cancer cell lines [50]. A recent study, during which chemical modifications of leelamine were made to identify its active site responsible for its anticancer activities, has shown that a suppression of the amino group or its charge may lead to a deletion of its antineoplastic actions, thus indicating that its lysosomotropic as well as its antitumorigenic effect may be mediated by this moiety [28].…”
Section: Chemistrymentioning
confidence: 99%
“…In melanoma cancer cell lines treated with leelamine, an inhibition of tumor development without significant systemic toxicity has been shown using various techniques, including modulation transfer spectroscopy MTS [3-(4,5-dimethylthiazol-2-yl)-5-(3-carboxymethoxyphenyl)-2-(4-sulfophenyl)-2H-tetrazolium] assay and liquid chromatography–mass spectrometry [43]; furthermore, a decrease in the proliferation and vascular development has been highlighted [48]. Nanolipolee-007, a liposomal form of leelamine, was also shown to reduce melanoma metastasis and to induce apoptosis [49]. Prostate cancer represents 25% of all cancers diagnosed in men and its incidence continues to rise in many countries; it is also the fifth most frequent cause of mortality among all the cancer types in men [57,58,59,60].…”
Section: Anticancer Effects Of Leelaminementioning
confidence: 99%